1991
DOI: 10.1056/nejm199101313240504
|View full text |Cite
|
Sign up to set email alerts
|

The Upper Limit of Physiologic Cardiac Hypertrophy in Highly Trained Elite Athletes

Abstract: On the basis of these data, a left-ventricular-wall thickness of greater than or equal to 13 mm is very uncommon in highly trained athletes, virtually confined to athletes training in rowing sports, and associated with an enlarged left ventricular cavity. In addition, the upper limit to which the thickness of the left ventricular wall may be increased by athletic training appears to be 16 mm. Therefore, athletes with a wall thickness of more than 16 mm and a nondilated left ventricular cavity are likely to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
498
9
39

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 889 publications
(593 citation statements)
references
References 38 publications
26
498
9
39
Order By: Relevance
“…The cardioprotector effect of the aerobic training is again observed when we verify that the ventricular cavity of the TT animals is relatively higher than in the ST animals. In an echocardiographic study (24) , the AAS increased the left ventricular wall thickness of elite athletes in more than 13mm, while mean increase in the cavity diameter was of 16mm. AAS stimulating effects on these cardiac dimensions have also been verified, including when compared with individuals who performed moderate resistance training (22) .…”
Section: Discussionmentioning
confidence: 99%
“…The cardioprotector effect of the aerobic training is again observed when we verify that the ventricular cavity of the TT animals is relatively higher than in the ST animals. In an echocardiographic study (24) , the AAS increased the left ventricular wall thickness of elite athletes in more than 13mm, while mean increase in the cavity diameter was of 16mm. AAS stimulating effects on these cardiac dimensions have also been verified, including when compared with individuals who performed moderate resistance training (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, athletes with MF may be more prone to cardiac remodelling. Several cross sectional (George et al, 2011;Pelliccia, Maron, Spataro, Proschan, & Spirito, 1991) and longitudinal studies (Arbab-Zadeh et al, 2014; 10 ± 1 12 ± 2 PWd (mm) 9 ± 1 11 ± 1 Diastolic function (Echo) E (cm/s) 65 ± 6 62 ± 10 A (cm/s) 60 ± 11 58 ± 5 E/A ratio 1.1 ± 0.3 1.1 ± 0.2 Septal E (cm/s) 10 ± 2 10 ± 2 A (cm/s) 11 ± 2 11 ± 1 Lateral E (cm/s) 11 ± 1 14 ± 3 A (cm/s) 11 ± 2 11 ± 1 Average E (cm/s) 11 ± 1 12 ± 2 A (cm/s) 11 ± 2 11 ± 1 E/E 6 ± 1 5 ± 2 Longitudinal strain (Echo) 2CH (%) −22.7 ± 1.9 −21.9 ± 4.4 4CH (%) −21.7 ± 2.9 −22.6 ± 3. 2CH: apical two chamber view; 4CH: apical four chamber view; APLAX: apical parasternal long axis view; E: early diastolic filling (E-wave); A: late diastolic filling (A-wave); E (cm/s): early diastolic velocity of mitral annulus; A (cm/s): late diastolic velocity of mitral annulus; S (l/s): systolic strain rate; E (l/s): early diastolic strain rate; A (l/s): late diastolic strain rate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of left and right ventricular volumes in athletes have shown physiological adaptation to training that differs from the pathological remodeling found in diseases such as hypertrophic and dilated cardiomyopathies (1)(2)(3)(4)(5). Furthermore, total heart volume (THV) has been shown to increase with long term endurance training, and there is a strong correlation between THV and peak oxygen uptake (VO 2 peak) (4).…”
Section: Introductionmentioning
confidence: 99%